Clinical efficacy of laparoscopic cholecystectomy combined with percutaneous transhepatic gallbladder drainage in severe acute cholecystitis: an analysis of prognostic risk factors - Chen, Lexiang; Hu, Mingfu; Huang, Shanhu; Sun, Yi (Frontiers in Surgery, 2025)
ObjectiveTo analyze the clinical efficacy of laparoscopic cholecystectomy (LC) combined with percutaneous transhepatic gallbladder drainage (PTGBD) in patients with acute critical cholecystitis.MethodsOne hundred patients diagnosed with severe acute cholecystitis were retrospectively selected and categorized into two groups based on the surgical approach: the joint group (n = 49, underwent LC combined with PTGBD) and the LC group (n = 51, underwent LC alone).ResultsThe joint group demonstrated a significantly shorter surgery duration and lower intraoperative blood loss compared to the LC group (P < 0.05). On the third postoperative day, patients in the joint group exhibited lower levels of WBC and CRP than those in the LC group (P < 0.05). The joint group showed faster recovery of bowel function, earlier ambulation, and shorter time to resume oral intake compared to the LC group (P < 0.05). Additionally, the joint group reported higher satisfaction than the LC group (P < 0.05). However, the joint group incurred higher surgical costs, total hospitalization costs, and medication costs than the LC group (P < 0.05). The independent risk factors for postoperative complications in patients with severe acute cholecystitis included a disease onset longer than 72 h, a surgical approach of LC alone, surgery duration longer than 2 h, intraoperative blood loss >100 ml, and age ≥65 years (P < 0.05).ConclusionCompared with LC alone, LC combined with PTGBD is more effective in reducing surgical trauma in patients with severe acute cholecystitis, improving postoperative inflammatory markers, and accelerating recovery. However, this combined approach is associated with significantly higher direct medical costs during hospitalization.